Socio-economic studies of Moringa oleifera L. leaf powder added to String Hopper Flour - Harshana, P.V.S.; Tennakoon, Asanka; Sandamal, Salinda; Sonali, Chamika (Plantae Scientia, 2018)
Recently, Moringa leaves substituted string hopper flour has been introduced to the market with regards to renewed consumer trend of healthy eating. However, the way consumer behaves towards this newly introduced product is questionable and hence it needs to be researched. Therefore, this study is mainly focused on evaluation of the consumer attitudes and acceptance of Moringa added string hopper flour. Study was consisted of a survey to evaluate the consumer attitudes. Moreover, a sensory evaluation was carried out to assess the sensory performance of the particular product. Collected data were mainly analyzed by using SPSS version 16. Interestingly, results showed that potential health benefits of Moringa remained prominent in the acceptance of the product. Further, sensory results showed appreciable sensory performance allowing consumers to purchase the product with sensorial intention. All the respondents (100%) were in satisfactory level regarding the product. Study demonstrates requirement of popularizing and elevating the availability of the product to achieve better market opportunities in order to widening the market Current study confirmed that the product exhibits potential of appreciable commercial acceptance and substantial purchasing capacity.